Toxicity of the sawdust used for phosphorus recovery in a eutrophic reservoir: experiments with Lactuca sativa and Allium cepa - Pantano, Glaucia; Mazzeo, Dania Elisa Christofoletti [UNESP]; Rocha, Thais Helena dos Santos; Marin-Morales, Maria Aparecida [UNESP]; Fadini, Pedro Sergio; Mozeto, Antonio Aparecido (Springer, 2021)
Eutrophication is one of the environmental problems arising from the increase of essential nutrient concentrations, mainly phosphorus and nitrogen. In contrast to excess phosphorus, the depletion of phosphate rock deposits used for the production of fertilizers compromises the food supply. Therefore, the development of technologies that propose the recovery of the phosphorus contained in eutrophic environments for its later use for agricultural fertilization purposes is very important to ensure global food security. This work aimed to evaluate the toxic potential of the sawdust (biosorbent previously used for phosphorus adsorption) in order to enable its application in agriculture. For this, toxicity experiments with Lactuca sativa (lettuce) and Allium cepa (onion) seeds were performed. The phytotoxic potential was assessed by means of the seed germination index and physiological parameters such as radicle and hypocotyl growth. Cytotoxicity, genotoxicity, and mutagenicity tests were also performed on onion seeds. From statistical tests, it was possible to affirm that the sawdust did not promote inhibition of seed germination and radicle and hypocotyl growth. No genotoxicity, cytotoxicity and, mutagenicity were observed, which allowed to state that the sawdust is not toxic to the onion species, which reinforces the possibility of application of the biosorbent for soil fertilization purposes. Therefore, the use of sawdust for phosphorus biosorption with the subsequent agricultural application is promising and quite important from a global food security point of view.
Keywords: Phosphate recovery; Eutrophication; Fertilization; Biosorbent; Phytotoxicity; Chromosomal aberrations